Prototype Sistem Monitoring Exhaust Fan pada Dapur Huni Berbasis Mikrokontroler - Dali Purwanto, Timur; Putra, Muhammad Riki Dwi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The purpose of this research is to detect the room temperature in the residential kitchen when the temperature of the residential kitchen becomes hot and to detect if there is smoke in the residential kitchen. The problem faced is because many residential kitchens in Indonesia have one or more stoves for cooking, which causes the temperature in the residential kitchen room to turn hot and cause smoke from the cooking. To overcome this problem, an Exhaust Fan is needed as an air conditioner so that the temperature remains stable. The method used in this research is quantitative by measuring the results of measurements and testing the percentage of errors. The results of the study found that the overall tool was working properly, measurements at component points had obtained results and the percentage of errors was not more than the maximum error, comparison of the output results on the Pzem-004t sensor and multitester had been measured with an error level not exceeding the maximum error, it can be concluded that the Pzem-004t sensor has good accuracy, and comparisons in point measurements using a multitester and on an LCD with an error level that does not exceed the error limit and have an accurate level of accuracy..